2D-3D integration of hexagonal boron nitride and a high-κ dielectric for ultrafast graphene-based electro-absorption modulators - Hitesh Agarwal (Nature Portfolio, 2021)
Here, three-dimensional hafnium oxide and two-dimensional hexagonal boron nitride are integrated in the insulating section of double-layer graphene optical modulators, leading to a maximum bandwidth of 39 GHz and enhanced modulation efficiency.